The Features Of Mental Health Status In Adolescents With Diffuse Nontoxic Goiter At Low Levels Of Vitamin B - Matkovska, T.; Volkova, Yu.; Kashkalda, D. (Psychiatry, Neurology and Medical Psychology, 2016)
In adolescents with diffuse nontoxic goiter observed dependence of the functional state of the thyroid gland and nervous system of the content of B vitamins. Half of the patients with low riboflavin and/or thiamine content registered often minimal thyroid insufficiency, autonomic dysfunction and neurotic disorders. The most significant changes in the functional state of the mental healts at low riboflavin were recorded in boys. The results indicate the advisability of including in complex treatment and prevention of adolescents with diffuse nontoxic goiter and accompanying pathology of the nervous system of B vitamins.